Rethinking Democratic Diffusion: Bringing Regime Type Back In. (February 2020) - Goldring, Edward; Greitens, Sheena Chestnut
Studies of democratic diffusion often emphasize geographic proximity: democratization in a country or region makes democratization nearby more likely. We argue that regime type has been underappreciated; authoritarian breakdown and democratization often diffuse along networks of similar regimes. A regime's type affects its vulnerability to popular challenge, and regime similarity increases the likelihood that protest strategies developed against one regime are effective against similar regimes. We employ a qualitative case study from China to generate our theory, then test it quantitatively and with out-of-sample cases. We find that regime similarity strongly predicts autocratic breakdown and democratic diffusion, making both outcomes more likely. Including regime similarity significantly reduces the effect of geographic proximity, although geographic proximity may increase the effect of regime similarity. Reinterpreting democratic diffusion as a regime-type phenomenon calls for revision to conventional wisdom on the role of international factors in authoritarian breakdown and democratization.